Structure, Properties, and Modification of Polytrifluorochloroethylene: A Review - Zou, Jiajia; Zhang, Maocheng; Huang, Mengqiu; Zhao, Dan; Dai, Yinhai (Frontiers in Materials, 2022)
Polytrifluorochloroethylene (PCTFE) is one of the earliest synthesized and commercialized fluoroplastics. It shows ultralow dielectric constant and loss coupled with other excellent properties such as good water vapor permeation resistance, anti-corrosion, light transparency, creep resistance and so forth, exhibiting great potential to break the bottleneck of the development of high frequency communication field. Besides, PCTFE-based materials have already been an essential role in some high-tech fields, including chemical, medical, aerospace and electrical industries. However, in the term of fundamental research, most of the reports concerning on the chemical and physical structure of PCTFE came from the last century, but very few in recent years. Herein, the history of the development and the research progress of the structure, properties and modification of PCTFE was introduced respectively and finally the perspective was proposed, aiming to provide guidance for the future research and application of PCTFE-based materials.